General constitutional principles and social security: practical applications (Revista do Tribunal Regional Federal da 3ª Região, 2015)
The work examines the concrete application of general constitutional principles in matters relating to social security law (the right to health, the right to social assistance and the right to social security).
Keywords: Social security×constitutional principles×practical applications×human dignity×legality×isonomy×due process of law×legal certainty×prohibition of retrogression×; social security; constitutional principles; practical applications; human dignity; legaly; isonomy; due process of law; legal certainty; prohibition of retrogression